Resposta :
Resposta:
6(x- 5) =4(x+3) +18
6x- 30= 4x + 12+ 18.
6x -4x= 30+ 12+ 18
2x= 60
x= 60/ 2
x= 30.
Explicação passo-a-passo:
confia ksksk
tem que separar os que tem x do que não tem, como foi feito.
✧ O valor de X = 30
--
Explicação passo-a-passo :
[tex] \\ { \large \displaystyle \sf {6(x - 5) = 4(x + 3) + 18}}[/tex]
[tex] { \large \displaystyle \sf {6x - 30 = 4x + 12 + 18}}[/tex]
[tex] { \large \displaystyle \sf {6x - 30 = 4x + 30}}[/tex]
[tex] { \large \displaystyle \sf {6x -4x = 30 + 30}}[/tex]
[tex] { \large \displaystyle \sf {2x = 60}} \\ [/tex]
[tex] { \large \displaystyle \sf {x = \frac{60}{2} }} \\ [/tex]
[tex]{ \blue{ \boxed{ \boxed{ \purple{ { \large \displaystyle \sf {x = 30}} }}}}} \\ [/tex]